Increasing Language Skills of Students from Low-Income Backgrounds : Practical Strategies for Professionals - Roseberry-McKibbin, Celeste (Plural Publishing Inc., 2013)
The second edition contains new information about using Response to Intervention (RtI) to serve low-SES students in general education classroom settings. Updated technology recommendations (e.g., using iPad and YouTube technology) are presented. The section on increasing the literacy skills of low-SES students has been expanded, as well. In sum, the second edition of Increasing Language Skills of Students from Low-Income Backgrounds is a must-have for any professional who serves students and their families from low-SES backgrounds.